Preferences of select attractants in the coating of onrab vaccine baits by rabies reservoir species - Johnson, S. R.; Berentsen, A. R.; Leland, B.; Oertli, E.; VerCauteren, K. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Rabies control managers and researchers in the United States are assessing how the Canadian vaccine ONRAB® may perform if integrated into the United States oral rabies vaccination (ORV) program. A measurement of success of any ORV program is bait uptake by target species. The attractant used in the bait matrix surrounding a vaccine influences bait uptake and vaccination rate. Our objective is to determine which flavor of attractant in the ONRAB® coating is the most preferred by rabies reservoir species in the field. In Texas (TX) we are evaluating four attractants (sweet, fish, egg, and cheese) in areas inhabited by raccoons (Procyon lotor), skunks (Mepthis mephitis), foxes (Urocyon cinereoargenteus), and coyotes (Canis latrans). In Puerto Rico (PR), we are comparing the preference of mongoose (Herpestes auropuctatus) for cheese, coconut, and fish attractants. We monitored bait stations with animal-activated cameras and regular checks of bait status (untouched, disturbed, and removed). In TX, we offered 540 baits of which 102 were removed, with cheese and fish most often removed (both 25%) followed by egg (21%) and then sweet (15%) and unflavored controls (14%). Image scoring from camera data is underway. In PR, mongoose removed baits on 38 of 343 occasions. Though all data are not yet fully analyzed, it appears mongoose prefer cheese, followed closely by fish. Findings in both TX and PR are suggesting that sweet flavors are least attractive to rabies reservoir species. To confidently state which attractants will likely perform the best, we need to complete the analyses of these data and do more extensive trials, especially in raccoon habitat in the eastern United States.